Hormesis in health and disease - Rattan, Suresh I. S.; Le Bourg, Éric (Oxidative stress and disease, 2014)
"Some mild stresses have positive effects on survival and aging as shown in animal models. There is also a large body of research that demonstrates these hormetic effects on aging, health, and resistance to severe stresses and diseases in human beings. However, the data are dispersed in the literature and are not always interpreted as hormetic effects. Hormesis in Health and Disease reviews the evidence for hormesis in humans as achieved through a variety of stresses or stimuli, and discusses mechanisms of hormesis and its ethical and legal issues."--